SPATIAL-TEMPORAL VARIABILITY OF HYDROCARBON DISTRIBUTION IN THE NORTHERN SECTOR OF THE BELAIT FORMATION - Ramli, Syamim (2010)
Spatial and temporal variability is the subject matter of interest in the Oil and Gas Industry. Recently, Padmanabhan (2010) indicated that the Belait Formation in North-eastern Sarawak showed tremendous spatial and temporal variability. By understanding this variability, improvements may be introduced to understanding reservoirs and its managements. The Belait Formation in North-eastern Sarawak represents the Middle – Upper Miocene age in the Miri Zone tectonostratigraphic. The Formation comprises alternating sandstone, sand and clays in varying proportions and thickness (Liechti et. al., 1960; Tate, 2001; Hutchinson, 2005) Traditionally the Belait Formation has been accepted as barren. However it has been discovered recently that hydrocarbons can be present in various forms in the Formation. The purpose of this research is to investigate further the occurrence of hydrocarbon and to characterize this aromatic hydrocarbon in the northern sector of the Belait Formation in Sarawak. Four representative samples were selected from an outcrop that had a stratigraphic height of about 100m. These samples were subjected to range of mineralo-chemical analysis and petrographical analysis. Fourier Transform Infrared spectra confirm the presence of aromatics in addition to free radicals and carboxyl group. This finding is further supported by variations of E4E6 ratios varying from 1.43 - 1.52. The x-ray fluorescence spectrometry indicates a high amount of oxygen, silica and aluminum indicating the presence of minerals such as kaolinite and quartz. Subordinate amounts of iron can be attributed to the presence of hematite or goethite. Powder diffraction data confirms the presence of the above weathered minerals in addition to traces of mineral such as titanium. Surface area estimations revealed that the presence of aromatic hydrocarbons attribute to the substantial increase of surface area. It is concluded that there is a spatial and temporal variability of appreciable sense of the hydrocarbon distribution in the northern sector of the Belait Formation. The presences of the aromatics are probably terrestrial and indicative of kerogen type III. However, the ongoing study to confirm the kerogen type is expected to be completed later this year.